Pendampingan Sistem Akuntansi dengan Microsoft Excel Macro untuk Penyusunan Laporan Keuangan berdasarkan SAK EMKM - Sari Mujiani; Median Wilestari (ACADEMICS IN ACTION Journal of Community Empowerment, 2022)
Usaha Barokah Isi Ulang only manually records purchases and income, with no adjustments to fixed assets or financial statements. As a result, the authors are eager to process the transaction data of Usaha Barokah Isi Ulang, as micro, small and medium enterprise (MSME) in order to generate a more precise financial report. The goal of this service is to provide more knowledge in creating financial reports based on SAK EMKM using the Microsoft Excel Macro accounting system, introduce the Microsoft Excel Macro accounting system, and assist in creating financial reports using the Microsoft Excel Macro accounting system. This program was provided at Usaha Barokah Isi Ulang at Jatisampurna Village, Bekasi on October-- December 2021. The lecture approach, question and answer method, and mentoring method are all used. According to the needs of the owner, the Microsoft Excel Macro accounting system can produce financial reports in a relatively quick, easy, and accurate manner for Usaha Barokah Isi Ulang.